The fate of neurons after traumatic spinal cord injury in rats: a systematic review - Hassannejad, Zahra; Zadegan, Shayan Abdollah; Shakouri-Motlagh, Aida; Mokhatab, Mona; Rezvan, Motahareh; Sharif-Alhoseini, Mahdi; Shokraneh, Farhad; Moshayedi, Pouria; Rahimi-Movaghar, Vafa (Mashhad University of Medical Sciences, 2018)
Objective(s): To reach an evidence-based knowledge in the context of the temporal-spatial pattern of neuronal death and find appropriate time of intervention in order to preserve spared neurons and promote regeneration after traumatic spinal cord injury (TSCI).